The Art of Performance : A Critical Anthology - Acconci, Vito; Bourdon, David; Brown, Cee S.; Burden, Chris; Butterfield, Jan; Enstice, Wayne; di Felice, Attanasio; La Frenais, Rob; Friedman, Ken; Goldberg, RoseLee; Gorsen, Peter; Henkin Melzer, Annabelle; et al. (New York : E.P. Dutton & Co, Inc., 1984)
Abramovic, Marina & Ulay ; Acconci, Vito ; Agnetti, Vincenzo ; Anastasi, William ; Anderson, Laurie ; Antin, Eleanor ; Armitage, Karole ; Ball, Hugo ; Bark, Jared ; Beckley, Connie ; Beuys, Joseph ; Bodanza, Gaetano K. ; Bogosian, Eric ; Brisley, Stuart ; Burroughs, William ; Burton, Scott ; Cage, John ; Chatham, Rhys ; Colette ; Cunningham, Merce ; Disband ; Dupuy, Jean ; Edelson, Mary Beth ; English, Rose ; Export, Valie ; Feminist Art Workers ; Fenley, Molissa ; Fox, Terry ; Friedman, Ken ; Gerz, Jochen ; Girouard, Tina ; Gray, Spalding ; Harrison, Helen & Newton ; Heyward, Julia ; Jonas, Joan ; Kipper Kids ; Knox, Sonia ; Kounellis, Jannis ; Kriesche, Richard ; Kushner, Robert ; Labowitz, Leslie ; Levine, Les ; Maciunas, George ; Maler, Leopoldo ; Marioni, Tom ; Meyers, Michael ; Miller, Larry ; Miller, Stephen Paul ; Miller, Tim ; Moorman, Charlotte ; Nice Style Pose Band ; Nitsch, Hermann ; Ontani, Luigi ; Oppenheim, Dennis ; Paik, Nam June ; Pane, Gina ; Parr, Mike ; Picabia, Francis ; Rainer, Yvonne ; Satie, Erik ; Schlemmer, Oskar ; Schloss, Arleen ; Schneemann, Carolee ; Schober, Helmut ; Schult, HA ; Shapiro, David ; Shiomi, Mieko (Chieko) ; The Theatre of Mistakes ; Tzara, Tristan ; Wilke, Hannah ; Wilson, Robert
Geselect. bibliog. p. 336-341
Engels
boek